2008
DOI: 10.1590/s1413-86702008000400011
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of wild-type varicella-zoster strains from India and the Oka vaccine strain using a VZV open reading frame - 62 based PCR-RFLP technique

Abstract: Since the introduction of varicella vaccination in India, surveillance of circulating VZV strains has gained significance. Differentiating wild-type VZV strains from the Oka vaccine strain can be achieved only by molecular genotyping methods. The development of PCR methods for VZV strain differentiation has been hampered by the fact that the VZV genome is highly conserved. We used VZV ORF 62 PCR-RFLP analysis to identify and differentiate wild-type VZV strains in India from the Oka vaccine strain. Digestion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Molecular detection methodologies are rarely needed for confirmation of VZV diagnosis. Therefore, only a few studies describing the VZV strain circulation pattern in India are available (Kaushik et al., 2008; Biswas et al., 2011; Chow et al., 2013). The studies were carried out to understand whether the strains circulating in three different states differed from the vaccine strain (Oka strain, Japan).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular detection methodologies are rarely needed for confirmation of VZV diagnosis. Therefore, only a few studies describing the VZV strain circulation pattern in India are available (Kaushik et al., 2008; Biswas et al., 2011; Chow et al., 2013). The studies were carried out to understand whether the strains circulating in three different states differed from the vaccine strain (Oka strain, Japan).…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to develop a vaccine that lacks the adverse events associated with Oka and is unable to establish latency have been based primarily on subunit vaccines consisting of recombinant viral glycoproteins , plasmid expression vectors , and viral vector vaccines . Although some have proven safe and immunogenic in animal models and a small number of human subjects, there are currently no data on their progression to clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Compiled using data from [135] [100,101] and present in all vOka haplotypes from varicella and zoster rashes [99,100,156,157]. As all three of these sites in ORF 62 were deemed equally robust at discriminating between vOka and wild type, some laboratories often only characterize one, either alone or in combination with the BglI and PstI sites [119,[166][167][168]. However, recent analysis of these three loci in Varivax-derived ORF 62 TA clones detected the wild-type allele on 2% of clones at position 107252 and on 6% of clones at 106262 and 108111 [100,169].…”
Section: Mutations Responsible For Attenuationmentioning
confidence: 99%
“…Characterisation of wt VZV and the Oka vaccine strains can be achieved only by molecular genotyping methods. In previous studies, the genotypic differentiations of vOka from wt VZV strains were based mainly on SNPs 69349 in ORF38 [17,18] or 105705 or 106262 in ORF62 [19][20][21][22][23][24]. However, a number of studies have shown that vOka vaccine preparations contain a mixture of virus strains leading to the recommendation that a set of four-markers in ORF62 should be used for diagnostic differentiation of wt VZV and vaccine-type VZV [25,26].…”
Section: Introductionmentioning
confidence: 99%